SPE Annual Technical Conference and Exhibition 2003
DOI: 10.2118/84565-ms
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tensile Strength Test Methodologies For Evaluating Oil and Gas Well Cement Systems

Abstract: Efforts to produce better annular isolation for oil and gas wells resulted in the development of methods to quantify the induced stresses that may occur within the cement sheath of a well. Along with the ability to calculate induced stresses in a cemented annulus, is the realization that typically, if there are sufficiently induced stresses to cause a mechanical failure of the set cement, failure will likely be of a tensile nature. While the ability to predict the compressive and the tensile stresses likely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Tensile failure occurs in lieu of failure in compression because the load is applied in an area of the specimen that is in a state of triaxial compression, allowing it to survive higher compressive stresses than would be achievable with a uniaxial compressive test. The indirect tensile strength is then calculated as follows: 13 have shown that, depending upon specimen size and aspect ratio, the STS method tends to give consistently higher tensile strength results than those measured with the DTS method. Since the cement sheath in the wellbore is exposed to a combination of compressive and tensile stresses it was decided for the purpose of this study the use of the STS results for modeling cement sheath failure would be reasonable.…”
Section: Splitting Tensile Strength Testingmentioning
confidence: 99%
“…Tensile failure occurs in lieu of failure in compression because the load is applied in an area of the specimen that is in a state of triaxial compression, allowing it to survive higher compressive stresses than would be achievable with a uniaxial compressive test. The indirect tensile strength is then calculated as follows: 13 have shown that, depending upon specimen size and aspect ratio, the STS method tends to give consistently higher tensile strength results than those measured with the DTS method. Since the cement sheath in the wellbore is exposed to a combination of compressive and tensile stresses it was decided for the purpose of this study the use of the STS results for modeling cement sheath failure would be reasonable.…”
Section: Splitting Tensile Strength Testingmentioning
confidence: 99%
“…The tensile strength and flexural strength tests of oil well cement is not yet standardized at atmospheric or downhole conditions. For this reason, it was carried out following the standards designated for concrete testing in the construction industry [ 34 ]. Firstly, the inner faces of the cement molds were cleaned and should be lubricated with a non-reactive releasing agent to make samples removal after curing easier.…”
Section: Materials and Research Methodologymentioning
confidence: 99%
“…For each tested age, the average test results on three samples from each concentration shall constitute the test result. After measuring the maximum axial load required to crush the cement sample, Equation (10) can be applied to calculate unconfined compressive strength, Equation (11) can be used to calculate the tensile strength [ 31 , 34 , 35 ] and Equation (12) can be used to calculate the flexural strength. where, is the unconfined compressive strength (MPa), Fmax is the maximum axial load (N), and D is the cement sample diameter (mm).…”
Section: Materials and Research Methodologymentioning
confidence: 99%
“…al. 12 reported the results of splitting tensile strength testing (ASTM Standard C 496-90) using various aspect ratios of samples and results from a direct unixial tensile strength testing method (ASTM Standard C-190-85). The work concluded that, dependent on the respective aspect ratios of the samples, the splitting tensile test results were on average 1.5 to 2.5 times higher than those generated using the direct unixial tensile strength method.…”
Section: Young's Modulus / Tensile Strength Determinationmentioning
confidence: 99%